The Role Of Artificial Intelligence In Analyzing And Interpreting Arabic Texts: Study On The Challenge Of Literal Versus Contextual Meaning/ دور الذكاء الاصطناعي في تحليل النصوص العربية وتفسيرها :دراسة في إشكالية الحمل على اللفظ والمعنى - Kadad, Mustafa; Şehitoğlu, Sadık (Ijaz Arabi Journal of Arabic Learning, 2025)
The Arabic language is widely recognized for its complexity and richness. It is distinguished by a sophisticated grammatical and rhetorical system that enables it to precisely convey a wide range of meanings. One linguistic phenomenon that has captured scholars' attention throughout history is the concept of "hammal ‘ala al-laugh wal hammal ‘ala al-mana" (literal and contextual interpretation). This phenomenon illustrates how language can combine the grammatical structure of phrases (form) with the intended meaning or context (content), creating a unique balance between grammatical rules and rhetorical creativity. In the modern era, with the rise of artificial intelligence (AI) and its various tools, Natural Language Processing (NLP) has emerged as a leading field of research focusing on understanding and analyzing languages using AI technologies. Despite significant advancements in this field, with its complexity and rich structure, Arabic poses a considerable challenge for these models, particularly in dealing with linguistic phenomena that rely on context and meaning, such as literal and contextual interpretation. This research bridges the gap between the rich Arabic linguistic heritage and modern technological advancements, opening new horizons for developing innovative tools to understand the Arabic language deeply. It also contributes to enhancing modern linguistic studies by demonstrating how AI can benefit from the depth of the Arabic linguistic tradition. The research aims to offer scientific contributions in applying AI techniques to study linguistic phenomena, expanding the use of AI in processing Arabic texts, which serves linguistic studies. While few studies combine these traditional phenomena with modern technological applications, the research can be categorized into two areas: traditional studies, which explore the concept of literal and contextual interpretation, and modern technical studies, which focus on challenges in Arabic language processing, particularly machine translation.